2015
DOI: 10.1371/journal.pone.0145754
|View full text |Cite
|
Sign up to set email alerts
|

Personalized Circulating Tumor DNA Biomarkers Dynamically Predict Treatment Response and Survival In Gynecologic Cancers

Abstract: BackgroundHigh-grade serous ovarian and endometrial cancers are the most lethal female reproductive tract malignancies worldwide. In part, failure to treat these two aggressive cancers successfully centers on the fact that while the majority of patients are diagnosed based on current surveillance strategies as having a complete clinical response to their primary therapy, nearly half will develop disease recurrence within 18 months and the majority will die from disease recurrence within 5 years. Moreover, no c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
126
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 144 publications
(134 citation statements)
references
References 17 publications
7
126
0
1
Order By: Relevance
“…These results are in agreement with imaging exams (CT scan and PET scan) showing no signs of disease and also with good overall clinical condition of the patient and highlight the applicability of using genomic rearrangement for building personalized tool for patient surveillance. After defining the genomic breakpoint of EWS-WT1 fusion, DSRCT patients can benefit from a highly specific test that has the advantage of a rapid turnaround time and potentially higher sensitivity in detecting disease progression earlier than imaging exams or other cancer antigens measurements, as reported for other tumor types [36, 37]. Monitoring through liquid biopsy is particularly attractive for solid tumors, which cannot be repeatedly sampled without more invasive procedures.…”
Section: Discussionmentioning
confidence: 99%
“…These results are in agreement with imaging exams (CT scan and PET scan) showing no signs of disease and also with good overall clinical condition of the patient and highlight the applicability of using genomic rearrangement for building personalized tool for patient surveillance. After defining the genomic breakpoint of EWS-WT1 fusion, DSRCT patients can benefit from a highly specific test that has the advantage of a rapid turnaround time and potentially higher sensitivity in detecting disease progression earlier than imaging exams or other cancer antigens measurements, as reported for other tumor types [36, 37]. Monitoring through liquid biopsy is particularly attractive for solid tumors, which cannot be repeatedly sampled without more invasive procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Specificity of each assay was first validated by quantitative PCR. Next, sensitivity and lower limits of detection were established by digital droplet PCR (RainDance Technologies, Billerica, MA), as we have previously described [25]. When no tumor DNA was available, positive controls were synthesized and used for these reactions as 300–500 bp gBlocks Gene Fragments (Integrated DNA Technologies, Coralville, IA).…”
Section: Methodsmentioning
confidence: 99%
“…We and others have previously shown that TP53 mutations can be detected in ctDNA from patients with advanced HGSOC and that, in a small number of patients studied, changes in ctDNA levels correlated with other clinical response measurements including CA-125 [21,2830]. However, in HGSOC the relationship of ctDNA to tumour volume, dynamic ctDNA changes during chemotherapy, and the relationship of early changes to outcomes during chemotherapy have not been characterised.…”
Section: Introductionmentioning
confidence: 94%